The Effect of Corporate Social Responsibility Program on Increasing Community Empowerment - Lumatul Faizah; Andre Dwijanto Witjaksono; Anang Kistyanto (Global Writing Academica Researching and Publishing, 2023)
In the business world, companies cannot only think about themselves but also need to guarantee the sustainability of life around the company’s operations, including the surrounding community. This research will be carried out to see the implications provided by Corporate Social Responsibility for the increase in community empowerment around the company area of PT. Kimia Farma, Kesamben Village, Jombok District, Jombang Regency. This research will be carried out using a descriptive quantitative approach. The research data was obtained through the results of filling out questionnaires by respondents with a total sampling of 97 samples using the Simple Random Sampling technique. The results of this study then found a significant influence that occurred simultaneously and partially between the social, economic, and environmental variables and the community empowerment variable. The researcher can say that the three independent variables significantly influence community empowerment.